Protective Effect of Vitamin D Supplementation on COVID-19-Related Intensive Care Hospitalization and Mortality: Definitive Evidence from Meta-Analysis and Trial Sequential Analysis - Christiano Argano; Raffaella Mallaci Bocchio; Giuseppe Natoli; Salvatore Scibetta; Marika Lo Monaco; Salvatore Corrao (MDPI AG, 2023)
Background: The COVID-19 pandemic represents one of the world's most important challenges for global public healthcare. Various studies have found an association between severe vitamin D deficiency and COVID-19-related outcomes. Vitamin D plays a crucial role in immune function and inflammation. Recent data have suggested a protective role of vitamin D in COVID-19-related health outcomes. The purpose of this meta-analysis and trial sequential analysis (TSA) was to better explain the strength of the association between the protective role of vitamin D supplementation and the risk of mortality and admission to intensive care units (ICUs) in patients with COVID-19. Methods: We searched four databases on 20 September 2022. Two reviewers screened the randomized clinical trials (RCTs) and assessed the risk of bias, independently and in duplicate. The pre-specified outcomes of interest were mortality and ICU admission. Results: We identified 78 bibliographic citations. After the reviewers' screening, only five RCTs were found to be suitable for our analysis. We performed meta-analyses and then TSAs. Vitamin D administration results in a decreased risk of death and ICU admission (standardized mean difference (95% CI): 0.49 (0.34-0.72) and 0.28 (0.20-0.39), respectively). The TSA of the protective role of vitamin D and ICU admission showed that, since the pooling of the studies reached a definite sample size, the positive association is conclusive. The TSA of the protective role of vitamin D in mortality risk showed that the z-curve was inside the alpha boundaries, indicating that the positive results need further studies. Discussion: The results of the meta-analyses and respective TSAs suggest a definitive association between the protective role of vitamin D and ICU hospitalization.